2015
DOI: 10.1002/acr.22474
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Functional Mobility Outcome Following Early Rehabilitation After a Total Knee Replacement: A Retrospective Study in Taiwan

Abstract: ObjectiveObesity is associated with an increased risk of osteoarthritis, and the incidence of obese patients requiring a total knee replacement (TKR) has increased in recent years. A high body mass index (BMI) may influence post‐TKR rehabilitation outcomes. We investigated the effects of obesity on functional mobility outcomes following post‐TKR rehabilitation in Asian patients whose BMIs were not as high as those reported in similar studies performed in non‐Asian countries.MethodsA total of 113 patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 60 publications
0
18
0
2
Order By: Relevance
“…These data may be surprising in that a number of sources have identified an elevated BMI as being correlated with decreased functional ability . The US Burden of Disease Collaborators calculated that an elevated BMI was the third leading risk factor for disability adjusted life years (DALYs), whereas the Health and Retirement Survey (HRS) found that persons over the age of 55 with a BMI above 30 had a shortened disability‐free life …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data may be surprising in that a number of sources have identified an elevated BMI as being correlated with decreased functional ability . The US Burden of Disease Collaborators calculated that an elevated BMI was the third leading risk factor for disability adjusted life years (DALYs), whereas the Health and Retirement Survey (HRS) found that persons over the age of 55 with a BMI above 30 had a shortened disability‐free life …”
Section: Discussionmentioning
confidence: 99%
“…These data may be surprising in that a number of sources have identified an elevated BMI as being correlated with decreased functional ability. 4,[13][14][15][16][18][19][20] The US Burden of Disease Collaborators 21 calculated that an elevated BMI was the third leading risk factor for disability adjusted life years (DALYs), whereas the Health and Retirement Survey (HRS) found that persons over the age of 55 with a BMI above 30 had a shortened disability-free life. 22 Given these associations between function and BMI within the general population, one may expect that during recovery from a TBI, the patients would have similar correlations with a reduced functional capacity and therefore reduced functional gains during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found no appreciable BMI function associations among patients whose body weight was normal to overweight; however, the decline in gait performance with increasing BMI was pronounced primarily among patients who were obese (.30 kg/m 2 ). When relating BMI to clinical outcomes, while studies in the fields of biostatistics and cardiology have advised against the categorization of BMI and advocated the use of nonlinear smoothed modeling (28,(44)(45)(46), existing TKA studies were conflicting and did not seem to heed this advice (10)(11)(12)(13)(14)(15). Accordingly, it is possible that some of the previous null or inconsistent findings may have resulted from not considering nonlinear effects (10)(11)(12) or from the categorization of BMI (14).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that women are more likely to develop knee osteoarthritis and that women awaiting TKA have greater physical disability than men (5)(6)(7)(8); however, it remains unclear if a sex difference in acute post-TKA physical outcomes exists. On the other hand, although a high BMI is a risk factor for both knee osteoarthritis and TKA (8,9), previous analyses of the influence of BMI on post-TKA performance-based physical function have reported conflicting results (10)(11)(12)(13)(14)(15). Because a nuanced understanding of the correlates and time course of knee impairments and performance-based physical function facilitates patient education, rehabilitation planning, and clinical decision making, we conducted a longitudinal study of a large sample of patients with TKA to 1) describe the time course of knee range of motion, quadriceps strength, and gait speed post-TKA and 2) to assess whether sex and BMI influenced the recovery of these measures.…”
Section: Introductionmentioning
confidence: 93%
“…Definitif cerrahi olan total diz artroplastisi (TDA) ileri yaştaki hastalarda en çok tercih edilen tedavi modalitesir. TDA'den sonra erken diz hareketi verip hastaya mobilize etmek esas olup çeşitli yardımcı rehabilitasyon programları ile bu süreç daha iyi yapılabilmektedir (39,40).…”
Section: Cerrahi Tedaviunclassified